Properties and evolution of dual and offset AGN in the ASTRID simulation at z ∼ 2. Issue 2 (20th March 2023) - Chen, Nianyi; Di Matteo, Tiziana; Ni, Yueying; Tremmel, Michael; DeGraf, Colin; Shen, Yue; Holgado, A Miguel; Bird, Simeon; Croft, Rupert; Feng, Yu
ABSTRACT: We examine the dual [both black hole (BH) active] and offset (one BH active and in distinct galaxies) active galactic nucleus (AGN) population (comprising ∼ 2000 pairs at 0.5 kpcΔ r30 kpc ) at z = 2 ∼ 3 in the ASTRID simulation covering (360 cMpc) 3 . The dual (offset) AGN make up 3.0(0.5) per cent of all AGN at z = 2. The dual fraction is roughly constant while the offset fraction increases by a factor of 10 from z = 4 ∼ 2. Compared with the full AGN population, duals are characterized by low M BH / M * ratios, high specific star formation rates (sSFR) of 1 Gyr^-1, and high Eddington ratios (∼0.05, double that of single AGN). Dual AGNs are formed in major galaxy mergers (typically involving M_halo10^13 M_ ), with simular-mass BHs. At small separations (when host galaxies are in the late phase of the merger), duals become 2 ∼ 8 times brighter (albeit more obscured) than at larger separations. 80 per cent of the bright, close duals would merge within 500 Myr . Notably, the initially less-massive BHs in duals frequently become the brighter AGN during galaxy mergers. In offset AGN, the active BH is typically ≳ 10 times more massive than its non-active counterpart and than most BHs in duals. Offsets are predominantly formed in minor galaxy mergers with the active BH residing in the centre of massive haloes (M_ halo10^13-14 M_ ). In these deep potentials, gas stripping is common and the secondary quickly deactivates. The stripping also leads to inefficient orbital decay amongst offsets, which stall at Δ r5 kpc for a few hundred Myrs.